2019
DOI: 10.1021/acs.joc.9b01212
|View full text |Cite
|
Sign up to set email alerts
|

Echingridimer A, an Oxaspiro Dimeric Sesquiterpenoid with a 6/6/5/6/6 Fused Ring System from Echinops grijsii and Aphicidal Activity Evaluation

Abstract: A new dimeric eudesmane sesquiterpenoid with an unreported 6/6/5/6/6 fused carbon skeleton, echingridimer A (1), and five monomers (2–6), including two new compounds (2 and 3), were isolated from the roots of Echinops grijsii. Their structures and absolute configurations were elucidated by comprehensive spectroscopic analyses and confirmed by X-ray crystallography or electronic circular dichroism spectra. Compound 1 represents the first example of a 3,15′-linked Michael-type adduct of two eudesmanes, which fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…niveum, P. infestans, C. gloeosporioides, and A. alternate). Among them, compared with the commercial fungicide carbendazim, compounds 9, 10, 31-33, 35, and 36 exhibited equal or better antifungal activity against six plant pathogenic fungi [23]. Importantly, the antifungal activities of dimeric dithiophene 47-49 were first reported by Wu Haibo et al The results showed that they had good antifungal activity against five plant pathogenic fungi.…”
Section: Anti-bacterial Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…niveum, P. infestans, C. gloeosporioides, and A. alternate). Among them, compared with the commercial fungicide carbendazim, compounds 9, 10, 31-33, 35, and 36 exhibited equal or better antifungal activity against six plant pathogenic fungi [23]. Importantly, the antifungal activities of dimeric dithiophene 47-49 were first reported by Wu Haibo et al The results showed that they had good antifungal activity against five plant pathogenic fungi.…”
Section: Anti-bacterial Activitymentioning
confidence: 98%
“…Specially, compounds 32 and 35 were the most potent thiophenes against M. incognita with LC 50 values 2.57 and 0.91 µg/mL in light, 1.80 and 0.86 µg/mL in dark, respectively [11]. Subsequently, Liu Tingting et al also reported that the new framework of sesquiterpene dimers 66 exhibited stronger insecticidal activity than sesquiterpene compounds 68-72, and even stronger insecticidal activity against aphids than the commercially available aphid fungicide pyrimethadone [23]. Additionally, Wu Haibo et al demonstrated for the first time that compounds 47-49 of dithiophene dimer had better nematicidal activity against Meloidogyne incognita than commercial nematicides ethoxyphosphorus, and had no phototoxicity [20].…”
Section: Insecticidal and Parasiticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation